442 The influence of HMGB1 gene (RS41369348) polymorphism on the susceptibility and clinical features of patients with IgAV. (11th October 2021) - Varga, Mateja Batnozic; Sestan, Mario; Wagner, Jasenka; Crkvenac, Kristina; Kifer, Nastasia; Frkovic, Marijan; Stefinovec, Laura; Grguric, Danica; Puseljic, Silvija; Jelusic, Marija
Abstract : IgA vasculitis (IgAV) or Henoch-Schönlein's purpura is the most prevalent systemic small vessel vasculitis in childhood, in which pathogenesis environmental and genetic factors play role. From genetic factors different studies proven that genes located inside the HLA region and gene polymorphisms located outside the HLA region contribute to the onset and different clinical features of IgAV. The aim of this study was to investigate the role of single nucleotide polymorphism (SNP)- rs41369348 (delT; chr13:30467220-30467227(GRCh38.p12)) for high mobility group box-1 (HMGB1) gene in the susceptibility and clinical features of patients fulfilling classification criteria for IgAV. In this study, we included 76 children with IgAV and 150 age- and sex-matched healthy controls without any history of autoimmune disease. After extracting genomic DNA from the whole peripheral blood, genotyping was carried by real-time PCR method using TaqMan SNP genotyping assays. Clinical data and laboratory parameters were collected for all IgAV patients. The normal T/T genotype was found in 83% of the IgAV patients and 91% of the control group. Heterozygous T/delT genotype was detected in 11% and 8% of the patient group and healthy controls, respectively. Homozygous mutant delT genotype was found in only 1 IgAV patient. Although there was higher frequency of heterozygous T/delT genotype of this gene polymorphism in IgAV group compared to control group, no genotype difference between those two groups was observed. No statistically significant differences in genotype nor allele were disclosed when patients with different IgAV clinical features were compared. Accordingly to our study, the HMGB1 gene polymorphism rs41369348 was not linked to increased susceptibility to childhood IgAV, its severity nor different clinical manifestations. SUPPORT: Croatian Science Foundation project IP-2019-04-8822